Retention and Attrition in U.S. STEM Education with the Help of computer Technology and Curriculum Development (International Journal of Scientific Research and Management (IJSRM), 2024)
The United States’ capacity to maintain a competitive workforce in a world driven by technology has been largely determined by the retention and attrition rates in STEM (science, technology, engineering, and mathematics) education. High attrition rates, especially among disadvantaged groups, remain a major obstacle despite initiatives to promote STEM areas. This study investigates how curriculum development and computer technologies can help with these problems. Teachers can design more individualized and interesting learning experiences by incorporating state-of-the-art technological tools like virtual labs, adaptive learning platforms, and AI-powered tutoring systems into the curriculum. Additionally, encouraging interest and retention in STEM subjects requires innovative curricula that prioritize project-based learning, multidisciplinary approaches, and real-world applications. This study identifies the obstacles to STEM education retention, assesses the efficacy of curriculum and technology initiatives, and suggests practical ways to reduce attrition. The study intends to shed light on how educational systems might better prepare students for success in STEM fields by utilizing case studies, data visualizations, and theoretical frameworks